Analisis Kinerja Supply Chain Manajement dengan Metode Supply Chain Operation Reference di PT. Sumber Jaya Indahnusa COY - Jekson Priadi Pasaribu; Uun Novalia Harahap; Denny Wallady Utama (CV. IRA PUBLISHING, 2022)
PT. Sumber Jaya Indahnusa COY is one of the companies in Indonesia engaged in the processing of palm oil with regional and domestic product marketing. PT. Sumber Jaya Indahnusa COY has problems related to the company's supply chain, where until now, the supply chain performance measurement management system is still not optimal. The measurements are still functional-based, carried out in each division or section in PT. Sumber Jaya Indahnusa COY. The solution to this problem is sought by measuring and improving the performance of the company's supply chain. The research method used is action research. Problem-solving is done using a supply chain operations reference approach. The results of supply chain performance measurement are 28 key performance indicators (KPI), namely 6 for the plan perspective, 8 for the source perspective, 4 for the make perspective, 6 for the deliver perspective, and 4 for the return perspective. The average total index value is 7.42. Based on the traffic light system, the index value is in the yellow category, indicating PT's supply chain performance. Sumber Jaya Indahnusa COY has not achieved the expected performance despite the results being close to the set targets.